Aplikasi Smart Water Filter Terintegrasi Panel Surya Untuk Penyediaan Air Bersih Pada Pondok Pesantren Tahfidzul Quran Saqona - Ali Musyafa'; Imam Abadi; Muhammad Khamim Asyari; Ardyas Nur Aufa; Muhammad Roy Ashiddiqi; Kafi Hannan Alhadi; Chairul Imron; Nisfatul Lamdia; Mochamad Raffi Isyanto (Pusat Publikasi ITS, 2026)
The Saqona Tahfidzul Quran Islamic Boarding School, Surabaya uses groundwater as its main source of clean water, which has not undergone a modern filtration process. This can cause health problems for students and Islamic Boarding School managers. One effort to overcome this problem is to provide a Smart Water Filter through community service. This community service aims to provide an energy-efficient and environmentally friendly clean water supply solution through the implementation of a solar panel-based Smart Water Filter at the Saqona Tahfidzul Quran Islamic Boarding School, Surabaya. The proposed technology allows for automatic and sustainable filtration of groundwater into usable water without relying on PLN electricity. The activity method consists of four stages, including: designing a reverse osmosis-based water filter mechanical system, designing a solar panel electrical system, designing a TDS monitoring system, and testing the Smart Water Filter. The results of the implementation of the TDS sensor-based Smart Water Filter showed accurate and precise performance with values ​​of 99.18% and 99%, respectively, with a decrease in TDS values ​​from 113–115 ppm to 105–107 ppm after filtration. Integration with solar panels has also been successfully carried out, so that the Smart Water Filter is proven not only effective in water filtration but also implements renewable energy sustainably.